Attitudes towards and barriers to writing advance directives amongst cancer patients, healthy controls, and medical staff. Issue 8 (2nd August 2005) - Sahm, S; Will, R; Hommel, G
Abstract : Objectives: After years of public discussion too little is still known about willingness to accept the idea of writing an advance directive among various groups of people in EU countries. We investigated knowledge about and willingness to accept such a directive in cancer patients, healthy controls, physicians, and nursing staff in Germany. Methods: Cancer patients, healthy controls, nursing staff, and physicians ( n = 100 in each group) were surveyed by means of a structured questionnaire. Results: Only 18% and 19% of the patients and healthy controls respectively, and 10% of the medical staff had written an advance directive. However, 50–81% of those surveyed indicated that they wished to write one. This intention was associated with deteriorating health (p < 0.001). Only 29% of the healthy controls and 43% of the patients knew about the possibility of appointing a health care proxy. A majority in all groups believed that advance directives may influence the course of treatment (79–85%), yet half of those surveyed in all groups fear that patients could be pressurised into writing an advance directive, and 38–65% thought that relatives could abuse such documents. Conclusions: Only a minority of the participants had written an advance directive and knew about the possibility of authorising a health care proxy. Deteriorating health was associated with increasing willingness to make a directive. Despite a majority belief that advance directives may influence treatment at the end of life, other factors limit their employment, such as fear of abuse.